Rancang Bangun Alat Ukur Tinggi dan Berat Badan Ideal Berdasarkan Metode Brocha Berbasis Mikrokontroler - Maulana, Luthfan; Yendri, Dodon (JITCE (Journal of Information Technology and Computer Engineering), 2018)
Body’s height and mass measurement usually are measured with a different instrument without a knowledge to know the ideal body mass index (BMI). Ideal BMI is related to our health condition especially for people who do exercise. Usually people just guess the BMI from a visual condition that sometime give a false measurement. This paper proposes a device that can measured ideal BMI based on Brocha method based on microcontroller. The body’s height will be measured using ultrasonic sensor while the body’s mass will be measured with a load cell. The results show that the proposed device can predict the BMI well. The height measurement has a successful rate of 80%.